Curriculum Development and Evaluation of the MBKM Program on Undergraduate Student Satisfaction - Ratih Hadiantini; Fitriani Reyta (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) program is a policy initiated by the Ministry of Education and Culture of Indonesia aimed at improving the quality of higher education through autonomous, flexible, and student-centered learning approaches. This study aims to analyze the impact of curriculum development and evaluation under the MBKM framework on student satisfaction levels in the Undergraduate Program of the Faculty of Economics and Business, Universitas Padjadjaran. The research employs a descriptive quantitative method with a survey approach using questionnaires. The results of this study are expected to provide deeper insights into student satisfaction regarding the implementation of MBKM and serve as an evaluation tool to enhance educational quality in higher education institutions, particularly in terms of service quality based on five dimensions: reliability, tangibility, responsiveness, assurance, and empathy.